A typology of sustainable circular business models with applications in the bioeconomy - De Keyser, Erika; Mathijs, Erik (Frontiers in Sustainable Food Systems, 2023)
As an approach to sustainable development, circular business models are increasingly being developed. However, many circular business models focus on environmental or technological contributions to sustainability rather than considering all dimensions of sustainability simultaneously. Based on existing sustainable business model archetypes, a hierarchical business model typology is developed that allows a stepwise exploration of sustainable business model innovation opportunities incorporating an environmental, social and economic dimension. An analysis of business model components generates a closer look on the six newly defined Sustainable Circular Business Models. Finally, a conceptual application for organic waste valorization technologies, supported by examples from literature, allows a practical view on the implementation of the business models in the bio-economy. The typology offers a guide toward sustainable business model design or innovation opportunities centered around technologies creating value from waste.